Analisis Perancangan Sistem Penerimaan Siswa Baru Menggunakan Framework Zachman - Aji, Ranggi Praharaningtyas; Hidayah, Debby Ummul (Universitas Diponegoro, 2019)
The zoning system is a new perspective that has been established by the government in supporting the acceptance of new students. However, the system turned out to be one of the obstacles in education. Because it was still not standardized and the school found it difficult to explain to the community. Seeing the existing problems, researchers try to provide a solution to combat the problems in the acceptance of new students. the solution is to make an online zoning system design. The method used in this research is the Zachman framework. The results obtained defines the entity to the system to be built, including student entities, register entities, UN entities, account entities and school entities. Furthermore, several processes that become the main processes in the online registration application include account creation, registration, announcement, registration validation, account management, and reports. Whereas in network analysis there is a topology update to make students able to access online registration applications wherever and whenever. The results of this study hopefully can be used as a reference for similar research.